KEGAGALAN REGIME NEGOSIASI FINAL PEACE AGREEMENT 1996 DALAM PELEMBAGAAN PENYELESAIAN KONFLIK MINDANAO - Surwandono ([Yogyakarta] : Fak. ISIPOL Universitas Gadjah Mada, 2011)
Mindanao's Conflict has been one of conflicts that notoriously perpetuated and unresolved. Negotiation regime of Final Peace Agreement 1996 - betweenthe government of the Philippmes under Fidel Ramos's administrative regime and MNLF with the leadership of Nor Misuari - has been presumably, by many scholars, a regime that acquainted with the features of resolving the c:onflict of Mindanao. Nevertheless, such negotiation regime of Final Peace Agreement 1996 remains failed to overcome the Mindanao\'s conflict. In this dissertational research, the writer exemplified instrumentalist approach in order to comprehensively analyze underlying factors of the negotiation regime of Final Peace Agreement 1996. Explaining the influential features of negotiation instrumentation to the regime's incompetency in the of conflict resolution in Mindanao, the writer argues that negotiation instrumentation has heen understood as consequential strategy to overcome the problematic of actors legillmacy and conflict of Mindanao iimultaneously. The negotiation instrUmentation by particular actors, however, gives shape to the option of the negOtIallOnregime and the compromising notion focusing more on underscoring the resolution of actors problematic rather than the deep-rooted problems of the Mindanao's conflict. The research used qualitative research methodology with case study as the ultimate strategy. Technique of collecting data was undertakeu with in-depth interview to several stakeholders in Mindanao\'s Ixmflict, negotiation practitioners as weJl as previous researchers whose competencies and specializations in this discourse. Besides, the research also underscored a series of interpretations of numerous documentations during negotiation process such as Tripoli Agreement 1976.1eddah Accord 1987, Final Peace Agreement 1996, and Republic Act 9045.